Bail reform and judical decision-making in New York City - Rempel, Michael (The journal of offender monitoring, 2023)
In 2020, New York City introduced a radical overhaul of its pretrial release protocols. Those changes are the subject of this in-depth analysis by Michael Rempel and Joanna Weill for the Center for Judicial Innovation. Their analysis probed deeply into the terms of New York’s bail reform legislation and its implementation in New York City. The reforms took effect just as Covid-19 disrupted every aspect of life in the city; within six months, as crime rates rose sharply, New York rolled back many of its new rules. While the pandemic complicated the picture, the results of New York’s extensive reforms were largely positive in many ways but unevenly applied from borough to borough and among the judiciary.